Impact of WTO on agriculture - T.D.S. Kumar, (Journal of Agricultural Extension Management, 2025)
The World Trade Organization essentially negotiates with the member countries and therefore, in a federal setup like India, we do not have specific role for the State Government to directly negotiate with WTO. In such a situation, the implications will have two layers, first layer at the State level, where the exportable originate and importable reach. Thus, the implications at the State level are the ground realities. The Central Govt, at the higher layer, which will negotiate with the WTO secretariat. As a result, the Ministry of Commerce in the Central government, will be involved in the negotiations, but the implications will be more concerned at the ground level either for the exporters, importers, consumers, producers or traders. Therefore, we chose to enlist the implications at two levels